(untitled) (Research, Society and Development, 2024)
Broad understanding of the “health and disease” process, respecting the “ethnic-cultural” peculiarities of indigenous peoples, in addition to the constant search for updates in health care. The objective is to describe the insertion of humanization in the nurses’ work with the indigenous people in the Amazon. This is an exploratory, descriptive literature review study aimed at the need for articulation of many indigenous peoples and political unity for common interests, changing the trajectory of extermination of these peoples, who in their history have always been articulated with ethnic resistance. 1st selection were 120 from the VHL, 115 from SCIELO, 100 from LILACS, 200 articles were excluded because they did not answer the keywords and were incomplete. in the 2nd selection, a total of 150 articles were filtered, 50 of which were from the VHL, 80 from Scielo, and 55 from LILACS, and 70 articles were excluded. ending in a 3rd and final filtering of basic articles, including 05 in the VHL, 05 in LILACS, and 05 in SCIELO, and 15 were excluded. Nurses must be active in the permanent work process, acting not only in the administration of activities, but rather be in constant interaction with the care/care environment, extracting elements, contributing and better identifying solutions to problems, and through their technical-scientific knowledge, developing humanization.